McDonald's USA : a restaurant icon's potential to thrive in a global pandemic - Mukherjee, Kaushik, (SAGE Business cases., 2022)
Over the past 65 years, McDonald's has grown to become the world's largest (McDonald's, 2020a) and most recognized fast-food restaurant company. Like other restaurant businesses during the COVID-19 pandemic, McDonald's was forced to confront how to survive. This was particularly true of McDonald's U.S. Company, McDonald's USA. McDonald's as a corporation originally achieved its industry dominance by leveraging a business model that relied on consistent operations, value, franchisor control of real estate, and a world-class supply chain. Over time, particularly in the United States, Canada, and Australia, McDonald's added additional features to its operating model.These items included drive-through windows, mobile order pickup, and delivery, all of which positioned McDonald's to successfully compete in the contactless environment mandated by the COVID-19 world. However, McDonald's direct fast-food competitors have similar advantages that afford them the same ability to take market share from fast-casual and full-service restaurants. The issue for McDonald's is how to maintain this market share momentum post COVID-19 and protect that share from direct competitors. Historically, McDonald's responds to these challenges by devoting high levels of capital spending on new locations, marketing, new products, and/or remodels, all of which add debt and take time to accomplish. McDonald's must seek solutions to combat the competition that are not capital intensive.